DAYA TARIK WISATA ALAM DI PULAU SENOA NATUNA KECAMATAN BUNGURAN TIMUR KABUPATEN NATUNA - Mita Purnamasari; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Senua Island is an located island not far from the village sepempang district bunguran Timur. The island is located in the south china sea bordering the eastern state of malaysia (north kalimantan). Senua Island is an area that has been set as a conservation area. This study aims to determine: (1) to describe the natural tourist attraction on the Senoa Island; (3) The government's efforts to develop tourist attractions In the senoa island.This study used a qualitative method with descriptive approach, this subjects of this study werw taken from Tourists, Tourism Awareness Chiefs, Tourism and Culture Offices and additional informants of the Fisheries Department.. The data collection is made by a study of documents, observation, interview, documentation.The results showed that the attractions of senua island has a natural tourist attraction like the natural beauty of the Senoa Island, natural beauty under the sea on the Senoa Island.. Other natural attractions such as cave birds nest besides the animals and plants on this island is not much so that the uniqueness of its own in this island. In addition, carrying out the activity that attracts the audience such as the release of hundreds of turtle children. The conclusion of this research is a tourist attraction Senoa Island has a natural tourist attraction that can be developed as a leading tourist and add existing facilities on the Senoa Island.Keywords : attraction, natural tourism, senoa island